Internal Locus of Control and Sense of Coherence Decrease During the COVID-19 Pandemic: A Survey of Students and Professionals in Social Work - Misamer, Melanie; Signerski-Krieger, Jörg; Bartels, Claudia; Belz, Michael (Frontiers in Sociology, 2021)
Mental health is severely challenged by the COVID-19 pandemic due to a variety of restrictions in public and private life. Students in particular may face additional and unique stressors: face-to-face classes have been largely replaced by digital formats, leading to further reduced social contacts, thus facilitating the development of psychological symptoms. In this study, we aimed to assess the impact of the current peri-pandemic situation on students' (1) locus of control and (2) sense of coherence, both of which have been linked to mental health in previous work. A total of 403 social work students from Germany participated, providing both retrospective (pre-pandemic) and current (February/March 2021) ratings. Furthermore, 324 social work professionals were included to analyze differences between both groups. Locus of control shifted significantly from internal to external during the pandemic for students and professionals. Furthermore, high mental burden correlated with increased external and decreased internal locus of control. Sense of coherence decreased during the pandemic for the entire sample and correlated with high mental burden. Overall, students showed a stronger drop compared to professionals, primarily due to a more pronounced decrease in perceived meaningfulness (all p < .001). In summary, students and professionals responded with increased feelings of powerlessness in the absence of sufficient coping strategies – this could lead to further deterioration of mental health as the pandemic continues. In this context, students appear to be particularly vulnerable to a reduction in sense of coherence. We conclude that interventions to improve coping strategies are urgently needed.